Numerical Simulation Study of Huff-n-Puff Hydrocarbon Gas Injection Parameters for Enhanced Shale Oil Recovery - Alsu Garipova; Elena Mukhina; Alexander Cheremisin; Margarita Spivakova; Anton Kasyanenko; Alexey Cheremisin (Energies, 2023)
Gas injection has already proven to be an efficient shale oil recovery method successfully tested all around the world. However, gas-enhanced oil recovery methods have never been implemented or tested for the greatest Siberian shale oil formation yet. This article proposes numerical simulation of a hydrocarbon gas injection process into a horizontal well with multiple hydraulic fractures perforating Bazhenov shale oil formation in Western Siberia characterized by ultra-low permeability. A complex field-scale numerical study of gas injection for such a formation has never been performed before and is presented for the first time in our work. The hydrodynamic compositional simulation was performed utilizing a commercial simulator. A sensitivity study for different operating parameters including cycle times, bottom-hole pressures for the production and injection period, and injected gas composition was performed after the model was history matched with the available production data. Some uncertain reservoir properties such as relative permeability curves were also sensitized upon. Two different ways of accounting for multiple hydraulic fractures in the simulation model are presented and the simulation results from both models are compared and discussed. Eventually, huff-n-puff injection of a hydrocarbon gas resulted in a 34–117% increase in oil recovery depending on the fracture model.